2022
DOI: 10.3390/cells12010094
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Proximal Tubule GLUT2—More than Meets the Eye

Abstract: Tubulopathy plays a central role in the pathophysiology of diabetic kidney disease (DKD). Under diabetic conditions, the kidney proximal tubule cells (KPTCs) are exposed to an extensive amount of nutrients, most notably glucose; these nutrients deteriorate KPTCs function and promote the development and progression of DKD. Recently, the facilitative glucose transporter 2 (GLUT2) in KPTCs has emerged as a central regulator in the pathogenesis of DKD. This has been demonstrated by identifying its specific role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Solute carrier family 2 member 2 (GLUT2) is a facilitative hexose transporter that mediates the transport of glucose, fructose, and galactose. Recently, GLUT2 has emerged as a central regulator in the pathogenesis of diabetic kidney disease ( Ahmad et al, 2022 ).…”
Section: Metabolism-related Proteinsmentioning
confidence: 99%
“…Solute carrier family 2 member 2 (GLUT2) is a facilitative hexose transporter that mediates the transport of glucose, fructose, and galactose. Recently, GLUT2 has emerged as a central regulator in the pathogenesis of diabetic kidney disease ( Ahmad et al, 2022 ).…”
Section: Metabolism-related Proteinsmentioning
confidence: 99%
“…In human hepatocytes, GLUT-2 is a glucose-sensitive gene along with genes encoding type 1 pyruvate kinase and S14 fatty acid synthase [ 5 ]. In these cells, glucose-induced transcription is achieved by activating carbohydrate response element binding protein (ChREBP) transcription factor [ 9 ].…”
Section: Basic Overview Of Glut-2mentioning
confidence: 99%
“…Interestingly, the group that discovered this mechanism also found that the GLUT-2 promoter lacks the carbohydrate response element ChoRE and instead contains the sterol response element SRE, which also binds sterol regulatory element-binding protein 1 (SREBP-1C) [ 10 , [17] , [18] , [19] ]. This transcription factor controls the transcription of lipogenic genes that require simultaneous regulation of insulin and blood glucose concentrations, and in the pancreas, it regulates GLUT-2 transcription more strongly than ChREBP [ 5 , 18 ]. Therefore, GLUT-2 expression is regulated by blood glucose concentration and adipogenesis factors, although additional regulatory factors beyond the above may be involved, waiting for discovery.…”
Section: Basic Overview Of Glut-2mentioning
confidence: 99%
See 1 more Smart Citation
“…47,52,55 The proximal tubule emerges as a major source (rather than a consumer) of glucose; it supports blood glucose through gluconeogenesis in the fasting state and by SGLT2mediated tubular reabsorption in the postprandial state. 56,57 These shifts are achieved by SIRT1 (which is upregulated as proximal tubular glucose declines), 58 by activation of AMPK (which increases fatty acid oxidation, ATP production, and Na 1 /K 1 -ATPase activity), [59][60][61] and by downregulation of HIF-1a. 38,62 Hence, the perinatal changes in metabolism and in nutrient signaling in the proximal renal tubule represent a shift from a fetal nutrient surplus to an adult nutrient deprivation state.…”
Section: Nutrient Surplus Signaling and The Fetal And Injured Adult K...mentioning
confidence: 99%